Use of solid-state H-2 NMR for studying protein-lipid interactions at emulsion interfaces - Areas, J; Grobner, G; Pellacani, L; Glaubitz, C; Watts, A (1997)
Interactions between myosin and β-casein with lipids at lipid-water interfaces were studied by solid-state 2H NMR using dimyristoylphosphatidylcholine with the four hydrogens at α- and β-positions (DMPC-d4) and the nine protons at the γ-position substituted by deuterium (DMPC-d9). Quadrupole splittings and spin-lattice relaxation times were used to describe the amplitude and rate of molecular motion of the choline segment, respectively, in liposomes made of pure labeled dimyristoylphosphatidylcholine or admixed with non-labeled dimyristoylphosphatidylglycerol (DMPG) in a 1:1 mole ratio. No changes were observed in these NMR parameters for the deuterons when increasing amounts of myosin were added to liposomes exclusively made of DMPC-d9 or DMPC-d4. However, when DMPG was present, myosin was found to interact electrostatically with the liposomes, and both the quadrupolar splittings and spin-lattice relaxation times of all head-group segments were affected, demonstrating that DMPG was necessary in the liposomes for the interaction to occur. The results suggest that positively charged lysine residues located at the tail domain of myosin provided the necessary sites for the lipid-protein interaction, leaving free the head domain for further structural interaction. On the other hand, β-casein was found to interact both with the charged (with DMPG) and neutral, zwitterionic (DMPC only) liposomes, although this interaction was more pronounced in the charged lipids. In the interaction with charged liposomes, β-casein was able to affect the lineshape of the NMR spectra from DMPC-d9 deuterons, even at low protein concentration (lipid/protein mole ratio = 30000:1), indicating its ability to locate at emulsion interfaces. © 1997 John Wiley and Sons, Ltd.